2014
DOI: 10.1021/nn406628s
|View full text |Cite
|
Sign up to set email alerts
|

Toward Structurally Defined Carbon Dots as Ultracompact Fluorescent Probes

Abstract: There has been much discussion on the need to develop fluorescent quantum dots (QDs) as ultracompact probes, with overall size profiles comparable to those of the genetically encoded fluorescent tags. In the use of conventional semiconductor QDs for such a purpose, the beautifully displayed dependence of fluorescence color on the particle diameter becomes a limitation. More recently, carbon dots have emerged as a new platform of QD-like fluorescent nanomaterials. The optical absorption and fluorescence emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
207
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(229 citation statements)
references
References 51 publications
11
207
0
2
Order By: Relevance
“…39,40 For conventional semiconductor QDs as fluorescence probes, it was found that those functionalized with long ligands were more cytotoxic than those with short ligands. 41 The EDA-carbon dots in this work were developed specifically as bright fluorescence probes of an ultra-compact configuration for related purposes, 20 and they were used in the labeling of MSCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 For conventional semiconductor QDs as fluorescence probes, it was found that those functionalized with long ligands were more cytotoxic than those with short ligands. 41 The EDA-carbon dots in this work were developed specifically as bright fluorescence probes of an ultra-compact configuration for related purposes, 20 and they were used in the labeling of MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Among more significant recent successes have been the finding and subsequent development of carbon "quantum" dots or more appropriately called carbon dots (for the lack of the classical quantum confinement effect in these nanomaterials), [4][5][6][7][8][9][10][11] which have played a leading role in an emerging and rapidly -3 -expanding research field centered on the design, preparation, and potential biomedical uses of various carbon-based QDs. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Carbon dots are generally small carbon nanoparticles with various surface passivation schemes by organic or bio-molecules (Figure 1), 4,6,7,12 where the more effective surface passivation has been correlated with brighter fluorescence emissions from the corresponding dots. The optical absorption of carbon dots is assigned to π-plasmon transitions in the carbon nanoparticle core of the dots, while the fluorescence emissions in the visible to near-IR are attributed to photogenerated electrons and holes trapped at diverse surface sites and their associated radiative recombinations.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al [90] firstly reported the utility of 13 CNMR spectroscopy in liquid state to identify the carbon states in a C-dots sample derived from candle shoot (Figure 8). Followed by this, numerous efforts have been contributed to using NMR spectroscopy in both solid state and liquid state for C-dots characterization [21,38,56,85,109,115,135,143,[159][160][161][162][163][164]. In addition, NMR has been proved to be powerful in the establishment of the 8 Journal of Nanomaterials chemical alterations that happened to the surface modifiers during carbonization.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%
“…These properties have led to a series of potential applications as in light emitting diodes [2,3], solar cells [4,5], sensing [6], catalysis [7], integration in photovoltaic devices etc. [8] and more importantly to a possible breakthrough in biosensing, bioimaging [9][10][11][12][13] and medical diagnosis [14].…”
Section: Introductionmentioning
confidence: 99%